Public space, common wealth developing transit-oriented, typology-based public spaces in Commonwealth Avenue's soon-to-rise MRT-7 University Avenue Station - Navarro, Joanna Samantha R.; Navarra, Nappy L.; Rosell, Auriga Joy B. (Quezon City College of Architecture, University of the Philippines Diliman, 2021)
As cities grow, traditional environments are being replaced by residential areas and commercial complexes -- a phenomenon that contributes to the growing problem of social segregation. Streets are inherently very public spaces, and thus could be accessed as more than just a thoroughfare for its users. Transit stations in these streets can be utilized and developed as public spaces. Currently undergoing construction, the Metro Rail Transit's Line 7 (MRT-7) will be in Commonwealth Avenue, an 18-lane highway in Quezon City. This study aims to turn one of its stations, the University Avenue station, into a public space that will be utilized by its neighboring facilities as well as the users of the train station. For data gathering, the study will use the Place Attachment Theory to analyze the psychosocial & sociocultural variables while the Space Syntax Theory of Natural Movement will be used to gather data for the built environment. For determining the site's spaces, the principle of Placemaking will be applied. Transit-oriented development (TOD) and station typology case studies are analyzed to provide key knowledge to the research.
include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Metro Rail Transit; Public spaces; Terminals (Transportation).